Antibiotics do not affect the degradation of fungicides and enhance the mineralization of chlorpyrifos in biomixtures - Castillo González, Humberto (2017)
The use of antibiotics in agriculture produces residues in wastewaters. The disposal of such wastewaters in biopurification systems (BPS) employed for the treatment of pesticides could result in the inhibition of the degrading capacity of the biomixtures used in the BPS. We assayed the effect of two commercial formulations of antibiotics used in agriculture, one containing kasugamycin (KSG) and the other oxytetracycline plus gentamicin (OTC+GTM), on the biomixture performance. Doses from 0.1 mg kg−1 to 1000 mg kg−1 of KSG increased the respiration of the biomixture, and low doses enhanced the mineralization rate of the insecticide 14C-chlorpyrifos. On the contrary, OTC+GTM depressed the respiration of the biomixture and the initial mineralization rate of 14C-chlorpyrifos; nonetheless, the antibiotics did not decrease overall mineralization values. The application of both formulations in the biomixture at a relevant concentration did not harm the removal of the fungicides carbendazim and metalaxyl, or their enhanced degradation; on the other hand, the biomixture was unable to dissipate tebuconazol or triadimenol, a result that was unchanged during the addition of the antibiotic formulations. These findings reveal that wastewater containing these antibiotics do not affect the performance of BPS. However, such a response may vary depending on the type of pesticide and microbial consortium in the biomixture.